Peningkatan Keselamatan Kerja Penderes Kelapa di Sentra Gula Merah Desa Lojejer, Kecamatan Wuluhan (Jurnal Suluah Komunitas, 2021)
This community service activity is carried out with the target group of coconut tappers at the Red Sugar Center, Lojejer Village, Wuluhan District, Jember Regency. This program has the aim of increasing the knowledge of coconut tappers about work safety, so that it will also increase the tresher's attitude and concern for their own safety at work. The problems faced by partners are 1) low knowledge of partners related to work safety, 2) cases of workers falling from heights which have fatal consequences for tappers. The resulting targets and outputs are 1) service products in the form of knowledge and attitudes in improving work safety, 2) awareness of the use of simple personal protective equipment. The methods used to achieve these goals are 1) socialization, 2) mentoring. This community service activity was attended by 12 people. The result of this activity is increased partner knowledge and increased awareness of partners in terms of work safety.